(3GdoYHGH aj TQM CHjGJ GdBOGHs - (3TQa GdOjf MSf Hf Ydj Hf UGdM GdaOhj (B((3GdYOhj(B)s; (3GHf TeS GdNdGaI , LYaQ Hf eMeO Hf CHh GdaVd (B((3TeS GdNdGag(B) (3eNJGQ GdGaVdj, eLO Gdedc,J (B622 (3g` s
(3ChdgG (B:s
(3aGfj deG hbaJ Ydi cJGH JCdja SfGA Gdedc hQCjJg bO YbH GdfKQ HGdfXe s
(3BNQgG (B:s
(3aoQH cFjH djS JfOi Lahfg hoQH cKjQ GdOeY ZjQ cFjH Je GdcJGH Hef Gddg Gdhdj GdhgGH s
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B128 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B149s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B26 s
Keywords: (3GdCOHs